3 - Religion, Economy and the Pre-colonial Dimensions of the Jos Conflict - Jacinta Chiamaka Nwaka, (Afrika Zamani, 2022)
Contrary to the popular view that the current Jos conflict is traceable to the effort of the Islamic leaders of the nineteenth century religious movement (jihad) to proselytise the people of the Jos Plateau, this article calls for the extension of the searchlight beyond religion. Using archival documents, oral interviews and secondary materials, it identifies the basis of the nineteenth century conflict between the local groups in the location of the present day Jos and the flag bearers of the Dan Fodio Jihad from the Bauchi Emirate not in religion, but in the latter’s attempt to exploit and dominate the region and its people economically through slave raiding, amana (tribute paying) relationship and some other means using religion. The article argues that almost a century of pre-colonial resistance to the Dan Fodio Jihad in the Jos Plateau, particularly by the three ethnic groups at the location of the present day Jos, does not find explanation in the people’s aversion to Islamic religion, but in the rejection of their economic exploitation by the flag bearers of the religious movement in the area.